Hydrothermal Pre-Carbonization Triggers Structural Reforming Enabling Pore-Tunable Hierarchical Porous Carbon for High-Performance Supercapacitors - Cuihua Kang; Mingyuan Zuo; Chang Qiu; Fanda Zeng; Yuehui Wang; Zhuo Chen; Tingting Liang; Daping Qiu (Batteries)
The engineering of pore structures has great significance in the development of high-performance carbon-based supercapacitor electrode materials. Herein, we have successfully transformed jujube pits into hierarchical porous carbon (HJPC-4) with excellent capacitive properties via a unique hydrothermal–carbonization–activation strategy. Hydrothermal pretreatment is essential to regulate the supermesoporous and macroporous structure of samples and their superior electrochemical performances. Owing to the large ion-accessible, remarkable supermesoporous and macroporous pore volume, HJPC-4 exhibited ultra-high specific capacitance (6 M KOH: 316 F g−1 at 1 A g−1; EMIMBF4: 204 F g−1 at 1 A g−1), excellent rate performance (6 M KOH: 231 F g−1 at 100 A g−1; EMIMBF4: 154 F g−1 at 30 A g−1), outstanding cycling stability (6 M KOH: the retention rate is 92.11% after 60,000 cycles at 10 A g−1; EMIMBF4: the retention rate is 80% after 10,000 cycles at 5 A g−1), and ultimate energy/power density up to 91.09 Wh kg−1/24.25 kW kg−1 in EMIMBF4 two-electrode systems. This work presents unique insights into the effect of the pore structure of carbon-based materials on their capacitive energy storage.